Variability of broomrape parasitizing on sunflower during its intensive cultivation in the regions of the Russian Federation - T. S. Antonova; N. M. Araslanova; M. V. Iwebor; S. L. Saukova (Аграрная наука Евро-Северо-Востока, 2024)
Annual monitoring of broomrape seed infestation of fields over the last 15 years shows that despite the widespread distribution of race G, seeds of other, weaker races E and F remain in many fields. The aim of the research was to identify the racial belonging of broomrape seeds from fields in sunflower-growing regions of the Russian Federation and to describe new botanical characteristics in representatives of the most widespread race G of the parasite. To identify the races, there were used the internationally accepted sunflower differential lines LC 1093, P 96, resistant to races A to F, as well as the original line RG, which is immune to race G and all previous races, hybrid NK Brio (resistant to races A to E) and hybrid Tunka (resistant to races A to G). A highly aggressive parasite biotype (future race H) has so far been identified in small numbers in some fields in the Krasnodar, Stavropol, Rostov, Voronezh, Samara and Orenburg regions. Obviously, the continuation of intensive sunflower cultivation in these fields will lead to a rapid spread of race H in these regions. In addition to the racial diversity, frequent changes in plant habitus (bushy forms) were observed in some representatives of race G. For the first time, there has been demonstrated an overgrowth of the haustorial-tubercle area of the parasite and the formation of multiple stems from a single tubercle. This creates an advantage in the competition for food between adjacent broomrape individuals on the same sunflower root and ultimately accelerates and increases the seed production of the plant. The rapid evolution of Orobanche cumana Wallr. during the intensification of sunflower cultivation is expressed not only in the formation of new physiological races, but also in an accelerated increase in the seed productivity of the parasite by changing the habitus of the plants, including the haustorial-tubercle area.